2019
DOI: 10.1039/c9tb00821g
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of short, charged peptide tags affects the temperature responsiveness of positively-charged elastin-like polypeptides

Abstract: Electrostatic and hydrophobic interactions between elastin-like polypeptides (ELPs) and non-ELP sequences affect the temperature responsiveness of ELP-based proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…We found that this extraction–precipitation–ITC method was able to reduce LPS levels below 1 EU/mL, a threshold that was not possible with ITC alone. This agrees with previous reports showing the necessity of alternative techniques to remove LPS when ITC is used to purify ELP from E. coli . We hypothesize that small amounts of organic solvent present in the extraction–precipitation samples help to solvate LPS in the aqueous phase and minimize its interaction with the aggregated ELP during ITC.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We found that this extraction–precipitation–ITC method was able to reduce LPS levels below 1 EU/mL, a threshold that was not possible with ITC alone. This agrees with previous reports showing the necessity of alternative techniques to remove LPS when ITC is used to purify ELP from E. coli . We hypothesize that small amounts of organic solvent present in the extraction–precipitation samples help to solvate LPS in the aqueous phase and minimize its interaction with the aggregated ELP during ITC.…”
Section: Resultssupporting
confidence: 92%
“…The ELP tag can be removed after purification by incorporating self-cleaving intein tags or retained, often with minimal effect on protein function. , ITC has emerged as an alternative to traditional purification by chromatography; however, it is still time consuming because it often requires at least 3–5 cycles to bring HCP levels below the threshold needed for in vivo applications. Each cycle is accompanied by target protein loss and is frequently unable to remove other macromolecular contaminants such as nucleic acids and LPS without additional purification steps. Although an additional precipitation of nucleic acids with polyethylenimine is frequently used, limitations have been reported when working with acidic ELP constructs. , The slowest and most labor-intensive aspect of ITC is the preparation of clarified lysate, particularly on a large scale where resuspension, complete lysis, and clarification can take hours. In addition, quick screening for expression is difficult across multiple conditions unless the fusion protein is easily and reliably detectable in the crude lysate.…”
Section: Introductionmentioning
confidence: 99%
“…The specific ELP sequence chosen was composed of 48 total pentapeptide repeats with equal amounts of lysine, tyrosine, and valine in the guest residue position ( Figure 1 ). One design (named ELP[YKV‐48] here but previously published as ELY 16 , [ 36 ] ELP[K 2 Y 2 V 2 ‐48], [ 37 ] or S‐tag[YKV‐48] [ 38 ] ) contained a commonly‐used composite tag composed of a T7 tag, a histidine tag, and an enterokinase cleavage site preceding the ELP sequence. ELP[YKV‐48] had many histidine and aspartic acid residues in the tag sequence (Figure 1 and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…ELP[YKV‐48] was described previously and was referred to as ELY 16, [ 36 ] ELP[K 2 Y 2 V 2 ‐48], [ 37 ] or S‐tag[YKV‐48]. [ 38 ] HD Ø ‐ELP[YKV‐48] was constructed previously and was referred to as I‐tag[YKV‐48]. [ 38 ]…”
Section: Methodsmentioning
confidence: 99%
“…Generally, increasing ELP molecular weight and concentration correspond to lower transition temperatures. [117][118][119] The phase transition can also be stimulated by other parameters that impact the hydrophobicity of ELPs, including but not limited to ionic strength, [119][120][121][122] pH, [120][121][122][123][124] solvent composition (Figure 2B), 115,125 and the local chemical environment generated by proteins fused to ELP. 126,127 Understanding of this broad parameter space, including monomer-scale sequence effects, 128 has enabled precise tuning of ELP phase transition temperatures and the development of novel ELP-based materials.…”
Section: Elastin Proteins: Thermally Responsive Elastomers With Tunable Phase Behaviormentioning
confidence: 99%